Effect of intensive psychological intervention on the psychological state and quality of life of patients with liver cancer (强化心理干预对肝癌患者心理状态和生存质量的影响) - HUANG Shuai (黄帅); LU LiHua (陆丽华) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of intensive psychological intervention on the psychological state and quality of life of patients with liver cancer. Methods A total of 108 patients who underwent resection for liver cancer from January 2020 to December 2021 were selected and randomly divided into the experimental group and the control group, with 54 cases in each group. The control group received conventional intervention methods, while the experimental group was given intensive psychological intervention on the basis of conventional intervention. The Short Form 36 (SF-36) Health Survey Questionnaire was used to evaluate the quality of life of patients before and 1 month after the intervention. The anxiety and depression status of patients were assessed by the Self-rating Anxiety Scale (SAS) and the Self-rating Depression Scale (SDS) respectively. Results Scores of SAS and SDS increased in both groups one month after intervention, and scores of SAS and SDS in the experimental group were lower than those in the control group (P＜0. 01). Dimension scores of SF-36 decreased in both groups one month after intervention, and dimension scores of SF-36 in the experimental group were lower than those in the control group (P＜0. 01). Conclusion Intensive psychological intervention is potentially effective to improve the quality of life and relieve the negative emotions such as anxiety and depression, which is beneficial to the postoperative recovery of patients. (目的 探讨强化心理干预对肝癌患者心理状态与生存质量的影响。方法 选择2020年1月-2021年12月医院收治的行肝切除治疗的肝癌患者108例, 随机分为试验组和对照组, 各54例。对照组采用常规护理干预方法, 试验组在常规护理干预的基础上采用强化心理干预。于干预前、干预后1个月采用中文版健康调查问卷(SF-36)评定患者生存质量, 采用焦虑自评量表(SAS)及抑郁自评量表(SDS)评估患者焦虑、抑郁等心理状态。结果 干预后1个月, 两组患者SAS和SDS评分均较干预前下降, 且试验组患者SAS和SDS评分低于对照组, 差异有统计学意义(P＜0. 01); 两组患者SF-36量表各维度评分较干预前提升, 且试验组SF-36量表各维度评分均高于对照组, 差异有统计学意义(P＜0. 01)。结论 强化心理干预能够有效改善肝癌患者的生存质量, 缓解患者焦虑、抑郁等不良心理状态, 有益于患者术后康复。)